Medication related problems among ambulatory patients with chronic kidney disease at St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia. - Eshetu Shiferaw Legesse; Oumer Sada Muhammed; Leja Hamza; Beshir Bedru Nasir; Teshome Nedi (PLoS ONE, 2022)
Background Medication related problem (MRP) is an event occurring, as a result, the medication therapy that actually or potentially interferes with desired health outcomes. Evidences reported that the prevalence of MRPs may result in a high burden of morbidity and decrease patients' quality of life. The problem is more significant among patients with chronic kidney disease (CKD) as a decline in kidney function and increase number of medications required to treat kidney disease and its complications. Thus, this study aimed to assess MRPs and its associated factors among patients with chronic kidney disease. Method Hospital-based cross-sectional study was conducted among 248 adult ambulatory patients with CKD (stage 1-4) at St. Paul's Hospital Millennium Medical College. Data were collected through patient interview and medical chart review from 1st of June to 30th of August 2019. MRPs were identified based on the standard treatment guidelines. Cipolle MRPs classification was used to classify the MRPs and Micromedex® was used as drug interaction checker. Binary logistic regression was utilized to identify the associated factors and p value <0.05 was considered as statistically significant. Result A total of 325 MRPs were identified from 204 (82.3%) study participants giving 1.6 MRPs per participant. One MRP was identified among 114 (55.9%) patients while two MRPs were identified among 64 (31.4%). The most common class of MRPs were need additional drugs 114 (35.1%) followed by non-compliance 54 (16.6%), unnecessary drug therapy 46 (14.2%) and dose too low 46 (14.2%). The two most common reasons for non-compliance were unaffordability of drugs 26(48.1%) and the lack of patient understanding about drug taking instruction 10 (18.5%). The study showed that only occupation (AOR = 5.2, 95% CI: 1.292-21.288, P = 0.020) and angiotensin converting enzyme inhibitor use (AOR = 6.6, 95% CI: 2.202-19.634, P = 0.001) had an association with the occurrence of MRPs. Conclusion The prevalence of MRPs among ambulatory patients with CKD was high and need of additional drug therapy was the commonest MRPs.